The effect of temperature and concentration on the inhibition of acid corrosion of carbon steel by newly synthesized Schiff base - Gurten, A. Ali; Keles, Hulya; Bayol, Emel; Kandemirli, Fatma (Elsevier BV, 2015)
Abstract Inhibition effect of Schiff base namely 1-(2-hydroxybenzylidene)-3-(2,5-dioxoimidazolidin-4-yl) urea (ALS) was studied on carbon steel corrosion in 1.0 M HCl by using the electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and linear polarization (LPR) and quantum chemical study. The values of activation energy (Ea), equilibrium constant (Kads), adsorption free energy ΔG°ads, adsorption enthalpy ΔH°ads and adsorption entropy ΔS°ads were discussed. The adsorption of inhibitor on metal followed Langmuir's adsorption isotherm. The thermodynamic parameters of adsorption reveal that there is a strong interaction between inhibitor and carbon steel. The highest inhibition efficiency was observed 5.0 × 10−4 M ALS concentration at 318 K. SEM and EDX observations confirmed the existence of protective inhibitor film on metal surface. Quantum chemical study supports the comparative inhibition effect of ALS.
Keywords: Corrosion; Schiff base; Carbon steel; Modeling study; Temperature; AFM; 3. Good health